Correlations between the expression of stromal cell activation related biomarkers, L-NGFR, phospho-ERK1-2 and CXCL12, and primary myelofibrosis progression - Székely, Tamás; Krenacs, Tibor; Maros, Máté E.; Bodor, Csaba; Daubner, Viktoria; Csizmadia, Annamaria; Vrabely, Brigitta; Timar, Botond (Pathology & oncology research, 2022)
In myelofibrosis, pathologically enhanced extracellular matrix production due to aberrant cytokine signalling and clonal megakaryocyte functions result(s) in impaired hemopoiesis. Disease progression is still determined by detecting reticulin and collagen fibrosis with Gomori’s silver impregnation. Here, we tested whether the expression growth related biomarkers L-NGFR/CD71, phospho-ERK1-2 and CXCL12 can be linked to the functional activation of bone marrow stromal cells during primary myelofibrosis progression. Immunoscores for all tested biomarkers showed varying strength of positive statistical correlation with the silver impregnation based myelofibrosis grades. The intimate relationship between spindle shaped stromal cells positive for all three markers and aberrant megakaryocytes was likely to reflect their functional cooperation. L-NGFR reaction was restricted to bone marrow stromal cells and revealed the whole length of their processes. Also, L-NGFR positive cells showed the most intersections, the best statistical correlations with myelofibrosis grades and the strongest interrater agreements. CXCL12 reaction highlighted stromal cell bodies and a weak extracellular staining in line with its constitutive release. Phospho-ERK1-2 reaction showed a similar pattern to CXCL12 in stromal cells with an additional nuclear staining in agreement with its role as a transcription factor. Both p-ERK1-2 and CXCL12 were also expressed at a moderate level in sinus endothelial cells. Connexin 43 gap junction communication channels, known to be required for CXCL12 release to maintain stem cell niche, were also expressed progressively in the myelofibrotic stromal network as a support of compartmental functions. Our results suggest that, diverse growth related pathways are activated in the functionally coupled bone marrow stromal cells during myelofibrosis progression. L-NGFR expression can be a useful biological marker of stromal cell activation which deserves diagnostic consideration for complementing Gomori’s silver impregnation.
Gesehen am 06.05.2024